The days for work. - Fagan, George, 1879-1907.; Holloway, Joseph, 1861-1944 (1902)
Black and white illustration on card with caption "The Days for work" written in manuscript hand in pencil underneath and signed by the artist "Ua Fagáin" at lower left within the illustration. Illustrration depicts a man holding a spade in his hand, bending down while digging; in the right background is a small cottage while in the left background are bushes and some trees; a mountain slope is visible in the distance. [The artist George Fagan also often signed his name "Ua Fágáin" and 'S. Uí Fhágáin'].
Keywords: Farmers -- Ireland -- 1900-1910.; Digging -- Ireland -- 1900-1910.; Cottages -- Ireland -- 1900-1910.; Men -- Clothing & dress -- Ireland -- 1900-1910.; Ink drawings -- Irish -- 1900-1910; Pen works -- Irish -- 1900-1910